Risky service experience? The role of risk in B2B customer journeys - Panina, Ekaterina; Jaakkola, Elina; Terho, Harri (Edward Elgar Publishing, 2025)
Although many prominent contemporary service contexts involve a high sense of risk for the customer, existing research on customer experience has seldom addressed risk. This chapter charts and examines the role of risk in service experience, focusing on B2B customer journeys that encompass purchase and usage processes by multiple individuals. By integrating the conceptual elements of B2B customer experience with three alternative viewpoints on risk, the chapter systematically examines how risk is connected with and may affect experiences, building towards a research agenda. These contributions support future empirical and conceptual research on risk in the context of service and customer experience.
Handbook of Service Experience